Correlations between Muscle Mass, Muscle Strength, Physical Performance, and Muscle Fatigue Resistance in Community-Dwelling Elderly Subjects - Elizabeth Elizabeth; Vitriana Vitriana; Irma Ruslina Defi (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: To determine the correlations between muscle mass, muscle strength, physical performance, and muscle fatigue resistance in community-dwelling elderly people in order to elucidate factors which contribute to elderly’s performance of daily activities.Methods: A cross-sectional study was conducted on community-dwelling elderly in Bandung from September to December 2014. One hundred and thirty elderly, 60 years old or above, were evaluated using bioelectrical impedance analysis to measure muscle mass; grip strength to measure muscle strength and muscle fatigue resistance; habitual gait speed to measure physical performance; and Global Physical Activity Questionnaire (GPAQ) to assess physical activity. Results: There were significant positive correlations between muscle mass (r=0,27, p=0,0019), muscle strength (r=0,26, p=0,0024), and physical performance (r=0,32, p=0,0002) with muscle fatigue resistance. Physical performance has the highest correlation based on multiple regression test (p=0,0025). In association with muscle mass, the physical activity showed a significant positive correlation (r=0,42, p=0,0000). Sarcopenia was identified in 19 (14.61%) of 130 subjects. Conclusions: It is suggested that muscle mass, muscle strength, and physical performance influence muscle fatigue resistance. Keywords: Community-dwelling, elderly, muscle fatigue resistance, muscle mass, sarcopenia DOI: 10.15850/ijihs.v4n1.684